Control of surface active agents content in aqueous environment by measuring surface tension - Kisil, I. S; R.T. Bodnar, R. T-; Patlovskyy, I. R.; Malko, O. H.; Kuchirka, Yu. M. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2014)
Surface tention (ST) is a physical-chemical parameter that informs about the presence of surface-active agents (surfactants) in the aqueous environment. The article proposes to obtain experimentally ST (IST) time dependence of the controlled aqueous environment and to judge by the equilibrium ST value (EST) about the surfactant concentration in such an environment, based on the previously received calibration dependence of EST on the concentration of respective surfactant in the aqueous environment. EST dependence of controlled aqueous environment is recommended to get though ST measurements by pulsing meniscus method based on the measurement of maximum pressure in the bubble (MPB) without its separation.The essence of pulsing meniscus method has been described. The advantage of this method over usual MPB method is that in the process of obtaining IST dependence and EST value one should use the same air meniscus surface at the end of metering capillary submerged in the sample of the investigated aqueous environment. It considerably speeds up the process of getting IST dependence and EST value of aqueous environment. The article contains a block diagram, appearance and work description of a device that implements pulsing meniscus method with the application of microcontrollers and hydraulic damper of depth of the metering capillary submersion in the controlled aqueous environment. Calculation of ST value on the basis of the measured maximum pressure drop ∆pmax in the meniscus pulsation process could be accomplished by one of the proposed dependences and methods (M. Cantor, R. Feustel, E. Schrödinger, J. Dugne, S. Sudgen, R. Bendure, I. Kisil). Recommended ranges of values for the parameter ∆ρgr ∆pmax have been demonstrated, where relative methodological error of the calculation results of ST values will not exceed 0.1%, where ∆ρ is the densities difference of the controlled aqueous environment and air, g is the acceleration of free fall and r is an outlet radius of the device metering capillary.